একজন ভারতীয় বাঙালির আত্নসমালোচনা - রহমান, মুহাম্মদ হাবিবুর (ঢাকা : মাওলা ব্রাদার্স, 2005)
Articles on 20th century intellectual life and social customs of Bengali (South Asian people) of India .
Includes index.
In Bengali.
Keywords: Bengali (South Asian people) -- Intellectual life -- 20th century; Bengali (South Asian people) -- Social life and customs -- 20th century